(untitled) (Global Journal of Medical Research, 2020)
The objective of this study was to develop a prebiotic beverage from yacon and pineapple sweetened with stevia. Nine functional beverage formulations were prepared. The yacon and the pineapple were incorporated in three proportions, P1: 30-70, P2: 50-50 and P3: 70-30, respectively. The selection of the optimal treatment was made by sensory analysis. The physicochemical analyzes of the optimal formulation evaluated were pH, acidity, total soluble solids, instrumental color and % Fructo oligosaccharides (FOS) (1-Kestose and Nystose). For the interpretation of results, a randomized design with a 3 x 3 factorial arrangement was used. Beverages P1 and P2, obtained the highest score on a scale of 9 points (p> 0,05); however, the latter had a higher percentage of FOS (0,19%). The beverage presented the following physicochemical characteristics, pH: 3,58 ± 0,03, Total soluble solids: 5 ± 0,01 ° Brix, Acidity: 0,36 ± 0,01%, Density: 1,02 ± 0,01g / ml, Viscosity: 13,55 ± 0,15 cP, Color Index: -14,03 ± 1,65 and FOS (1-Kestose: 0,06% and Nystose: 0,13%).